Analysing gender equality at the firm level - Dania Eugenidis; Jan Kinne; David Lenz (Philipps-University Marburg, School of Business and Economics, 2022)
The role of gender in the labour force and potential inequalities between men and women have been widely discussed. Despite efforts to align gender roles in recent decades, high levels of inequality are not an exception but rather the standard. These inequalities can lead to the respective minorities' general dissatisfaction, which affects the working atmosphere and ultimately a firm's economic success (Hoogendoorn et al. 2013). Recent quantitative studies confirm this dissatisfaction exists. However, analyses only take place at a country or regional level. Therefore, conclusions can be drawn on an aggregated level, whereas underlying structural differences between individual firms remain undetected. Alternative ways to measure inequalities include qualitative studies for individual companies. However, no generalized inference can be made. Our proposed framework, the Gender Equality Firm Index (GEFI), allows for quantitative gender equality analysis at the company level. GEFI aims to explore the latent and the concrete implementation of gender equality in firms. Specifically, we derive firm-level measurements from large-scale data extraction of firm websites and combine them with official data. We consequently derive a gender equality score for each company, making it possible to draw conclusions at any given level of granularity. We demonstrate the applicability of our framework in a case study including nearly 1 million firms throughout Germany. Thereby, we find that mainly urban and western German firms in sectors such as health and social services comparably enforce gender equality the most, which is in line with the existing literature.
Keywords: 330; Gender Equality Index; Firm level studies; Web Minig; Germany; Gender